Legal Formulation of Marriage of Different Religions for the Benefit of Society - Dian Septiandani; Dharu Triasih; Dewi Tuti Muryati (Hang Tuah Law Journal, 2017)
Different religious marriages are a problem for society. Indonesia is a country with the majority of the world's largest Muslim population issues concerning marriage is still common. There is a need for proper legal formulation for interfaith marriage as an effort to minimize any adverse impacts arising in different religious marriages.